Pharmacovigilance and Adverse Drug Reaction Reporting by Nurses to Improve Patient Safety Goals at Hospital in Bekasi, West Java - Eff, Aprilita Rina Yanti; Utami, Luciana Mery; Indrawati, Ratna (Unnes Journal of Public Health, 2024)
Nurses are frontline healthcare providers who spend much time with patients and can help avoid, mitigate, promote public health, and determine and maintain medicine safety. To ensure patient and medication safety, nurses need knowledge and experience in Pharmacovigilance. This study aims to assess Pharmacovigilance and adverse drug reaction reporting by nurses to implement Patient Safety Goals with Patient Safety Culture as intervening variables at X Hospital in Bekasi. This research is a quantitative causality study with a cross-sectional design to see the effect of pharmacovigilance knowledge on implementing patient safety goals mediated by patient safety culture. The study was conducted on 130 nurses at X Bekasi Hospital who met the inclusion and exclusion criteria. The data collection technique uses a closed questionnaire instrument; the answers to the questionnaire questions have been determined. Data were analyzed using the Smart PLS program's Structural Equation Modeling technique. The study's results found that knowledge of Pharmacovigilance and adverse drug reactions significantly affected the implementation of patient safety goals (F count is greater than F table / 64.5> 2.67; (R²) = 0.667). There is a significant influence of pharmacovigilance knowledge on improving patient safety culture (p-value = 0.000). The estimated value of the influence of pharmacovigilance knowledge on patient safety culture is 60.9%. Knowledge, attitude, and practice of Pharmacovigilance is the dominant variable in influencing patient safety culture and positively influences the implementation of patient safety goals. However, knowledge, attitude, and practice significantly impact patient safety culture, so efforts to implement consistent and continuous Pharmacovigilance can improve patient safety culture, which will continue with implementing patient safety goals.